Damage and failure of Orban’s gun during the bombardment of Constantinople walls in 1453 (Fracture and Structural Integrity, 2019)
In this paper the bombardment of the Constantinople Theodosian Walls by the great cannon of Orban is numerically reproduced deploying Structural Mechanics. Overall gun dimensions were assessed based on historical reports, whereby, the gunpowder charge p was estimated at 177 kg, and the gun was placed at 500 m from the Inner Walls. Gun ballistics and effect on target have been evaluated analytically. The analysis has verified Orban’s gun muzzle velocity, cannonball trajectory and its effect on Constantinople Walls by successfully calculating the length of the breach in the wall, referred in historical reports, as well as the cannon ball penetration into soil. The evaluated sound pressure level inside Constantinople, produced by the bombard, confirmed the tremendous psychological effect of the cannon’s blast on the City’s population. A numerical effort was made to assess the combined effect of powder chamber internal pressure with associate temperature produced by powder ignition.
Keywords: Bombard damage; Medieval gun ballistics